Multidisciplinary Team Meeting in the Core of Nasopharyngeal Cancer Management Improved Quality of Care and Survival of Patients - Kartika W Taroeno-Hariadi; Camelia Herdini; Aulia S Briliant; Henry K Husodoputro; Wigati Dhamiyati; Sagung Rai Indrasari; Setiyani P Lestari; Yulestrina Widyastuti; Herindita Puspitaningtyas; Risa Rahmasari; Innayah Nur Rachmawati; Ibnu Purwanto; et al. (SAGE Publishing, 2023)
Nasopharyngeal cancer (NPC) cases are often diagnosed in advanced stages. The complexity of clinical management for advanced-stage NPC requires thorough communication and shared decisions between medical professionals and allied teams. Incorporating a multidisciplinary team meeting (MDTM) for newly diagnosed NPC patients was chosen to facilitate collaboration and communication between physicians. This retrospective study aimed to compare the quality of care, clinical responses and survival between NPC patients treated with and without MDTM. Data on clinical responses, assessment visits, date of progression and death with progression-free survival (PFS), overall survival (OS), and hazard ratio (HR) were collected and analyzed with 95% confidence interval (CI) and significance set as P  < .05. There were 87 of 178 NPC patients treated with MDTM. Revisions of diagnosis and stage occurred in 5.7% and 52.9% of cases during the MDTM. More clinical responses were achieved by patients treated with MDTM (69.0%vs 32.0%, P  < .00). NPC patients who received MDTM treatment recommendation had a lower risk for progression (median PFS 59.89 months vs 12.68 months; HR 0.267, 95% CI: 0.17-0.40, P  < .00) and mortality (median OS was not reached vs 13.44 months; HR 0.134, 95% CI: 0.08-0.24, P  < .00) compared to patients without MDTM. Incorporating the MDTM approach into NPC management improves patients' clinical responses and survival.